Late asthmatic response to inhaled glacial acetic acid. Issue 7 (July 1994) - Kivity, S; Fireman, E; Lerman, Y
Abstract : A patient with bronchial asthma who developed a late asthmatic response to inhalation challenge with glacial acetic acid is presented. This is believed to be the first description of a reaction to this allergen in an asthmatic patient.